An analysis of the professional formation, organization and functioning of volleyball in the physical education schools in Parana State - Neves, Roberto Garcia (Journal of Physical Education (Maringá), 2008)
The aim of this research was to find out and analyse the professional formation offered as well as the organization and functioning of volleyball teaching in Schools of Parana. Questionnaires were applied to volleyball teachers and to the Physical Education Departaments of cash discipline. We got answers to all questions made. By the results we got the conclusion that the aim in teaching planning and the contents in the discipline made it marely pedagogical and that the majority of the teachers directed their theaching of pass, raising, cute, blockade, serve and the system of attack and defence to pedagogical formation.